1974
DOI: 10.1159/000251498
|View full text |Cite
|
Sign up to set email alerts
|

Topical Vitamin A Acid (Airol®) and Systemic Oxytetracycline in the Treatment of Acne Vulgaris

Abstract: A double-blind, controlled multi-centre trial with 238 patients was employed to study the relative merits of three treatment schedules in acne vulgaris. Schedule A consisted of oral oxytetracycline and topical vitamin A acid cream (0.05%), schedule B of oral oxytetracycline alone, and schedule C of vitamin A acid alone. Large and statistically significant reductions occurred in the number of come dones, papules and pustules during 8 weeks of therapy, which could be attributed neitherto placebo effects nor to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…It is worth emphasizing that the clinical impression previously mentioned [2] -according to which the therapeutic effect of retinoic acid is not correlated to the local intolerance of the preparation -has been confirmed by the present trial.…”
Section: Commentsupporting
confidence: 81%
See 2 more Smart Citations
“…It is worth emphasizing that the clinical impression previously mentioned [2] -according to which the therapeutic effect of retinoic acid is not correlated to the local intolerance of the preparation -has been confirmed by the present trial.…”
Section: Commentsupporting
confidence: 81%
“…They constitute a rather big group which might probably tolerate Ro 11-1430 better. The ethanol-propylenglycol lotion used in these trials has a more pronounced local irritative effect than the oil-in-water emulsion cream used in previous trials [1,2], and the retinoic acid derivative should also be available in such an ointment base.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of combining a retinoid plus antimicrobial therapy was first investigated in the 1970s. [96][97][98][99] Several early small studies showed that the combination of a retinoid plus an antimicrobialeBPO, topical antibiotics, and oral antibioticsewas more effective than monotherapy with the antimicrobial. 96,99,100 For example, Mills et al 96 reported that the combination of tretinoin plus oral tetracycline resulted in a good to excellent response in 67% of patients vs 48% of those treated with tretinoin alone and 41% of those treated with tetracycline alone.…”
Section: Retinoid-based Combination Therapy For Acnementioning
confidence: 99%
“…Controlled clinical trials have demonstrated that topical treatment with retinoic acid is superior to placebo in patients with acne vulgaris [1] and at least as good as systemic administration of Oxytetracycline [2]. Erythema and desquamation, however, occur with a high frequency.…”
mentioning
confidence: 99%